TINGKAT KEJADIAN Avian Influenza PADA UNGGAS MATI DI KOTA YOGYAKARTA TAHUN 2012 â 2013 BERDASARKAN LAPORAN PETERNAK - , GALUH INDARTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Avian Influenza (AI) is a disease that attacks on aves. This disease initially identified in ducks , but due to antibodies in ducks is quite resistant , so rarely found dead duck as AI , but just then ducks transmit the disease to other poultry likes chickens and turkey. Recently incidence of Avian influenza is much reduced when compared to the events that occurred in the 2000s . This study aimed to determine the incidence of avian influenza around the city of Yogyakarta is based on reports from farmers , then followed up by the Department of the Industry, Trading, Cooperation, and Agriculture Yogyakarta District in 2012 â 2013. Data from the Office of the Industry, Trading, Cooperation, and Agriculture, Yogyakarta District, indicates that the incidence of AI around the city of Yogyakarta in 2012 by 13,8 % and by 2013 9% were reported by farmers. Department conducted an inspection directly to the suspect AI and test samples with test Rapid test. From these data it can be concluded that the incidence of AI were reported by farmers in Yogyakarta, has decreased in 2013.